Edukasi Isi Piringku Sebagai Pemenuhan Gizi Seimbang di Masyarakat Nelayan Kota Tegal - Oktariani Pramiastuti; Ratna Widhiastuti; Anggit Pratiwi; Eni Purwiastuti; Grace Monica; Aurelia Neysa Putri Nirwana; Radinka calista Anggita; Siti Rachmalia; Yudistira Rifki Ramdhani (UNIVERSITAS BHAMADA SLAWI, 2026)
Public health status can be assessed through various factors, including life expectancy, mortality rates, morbidity rates, and nutritional status. One way to improve health status is by enhancing the community's nutritional status. The